Uganda’s Infrastructure : A Continental Perspective - Ranganathan, Rupa; Foster, Vivien (2012)
Uganda has made substantial progress on its infrastructure agenda in recent years. The early and successful ICT reform detonated a huge expansion in mobile coverage and penetration resulting in a highly competitive market. Power sector restructuring has paved the way for a rapid doubling of power generation capacity. Uganda is doing well on the water and sanitation MDGs, and has made effective use of performance contracting to improve utility performance. However, a number of important challenges remain. Despite reforms, the power sector continues to hemorrhage resources due to under-pricing and high distribution losses, while electrification rates are still very low. Providing adequate resources for road maintenance remains a challenge, and further investment is needed to increase rural connectivity and improve road safety. Addressing Uganda's infrastructure challenges will require sustained expenditure of around $1.4 billion per year over the next decade, strongly skewed towards capital expenditure. Uganda already spends approximately $1 billion per year on infrastructure, equivalent to about 11 percent of GDP. A further $0.3 billion a year is lost to inefficiencies, the bulk of which are associated with underpricing and distribution losses in the power sector. Uganda's annual infrastructure funding gap is about $0.4 billion per year, most of which is associated with irrigation as well as water and sanitation infrastructure.